Limits and application of the principle of opportunity in crimes against minors (2022)
This article addresses the institutional, regulatory, judicial limits and the legal prohibitions to apply the principle of opportunity in crimes against minors, from the Childhood and Adolescence Code, as well as the reforms to the Criminal Procedure Code. Consequently, the legal and jurisprudential development that has sustained the impossibility of resigning, suspending or interrupting the criminal action in cases of serious crimes against minors will be explained. However, despite the existence of express legal prohibitions, it will be argued why it is possible to fully apply the principle of opportunity in cases in which the legal prohibitions contradict norms, principles and values ​​of constitutional hierarchy. In this vein, it will be justified that in those cases in which the prohibition of applying the principle of opportunity leads to the violation of the principle of proportionality, fundamental rights and the constitutional principles of criminal law, the exception of unconstitutionality should be applied. to respect the supremacy of the Political Constitution.